2023
DOI: 10.1096/fj.202201846rr
|View full text |Cite
|
Sign up to set email alerts
|

Acute, next‐generation AMPK activation initiates a disease‐resistant gene expression program in dystrophic skeletal muscle

Abstract: Duchenne muscular dystrophy (DMD) is a life‐limiting neuromuscular disorder characterized by muscle weakness and wasting. Previous proof‐of‐concept studies demonstrate that the dystrophic phenotype can be mitigated with the pharmacological stimulation of AMP‐activated protein kinase (AMPK). However, first‐generation AMPK activators have failed to translate from bench to bedside due to either their lack of potency or toxic, off‐target effects. The identification of safe and efficacious molecules that stimulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Thus, we speculate that most of the effects of LEDT and IDE treatment on muscle regeneration capacity are mediated by the AMPK pathway. A recent study reported that the AMPK activation in the skeletal muscle of mdx mice evokes several signaling pathways, such as the increase of the autophagy signaling and modulation of the expression of myogenic regulatory factors that promote a disease-resilient phenotype in DMD [ 51 ]. In addition, it has been demonstrated that AMPK stimulation led to some beneficial effects in the skeletal muscle of DMD experimental models, including the reduction of skeletal muscle fragility and induction of slow-twitch myogenesis, which make the muscle phenotype more oxidative [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate that most of the effects of LEDT and IDE treatment on muscle regeneration capacity are mediated by the AMPK pathway. A recent study reported that the AMPK activation in the skeletal muscle of mdx mice evokes several signaling pathways, such as the increase of the autophagy signaling and modulation of the expression of myogenic regulatory factors that promote a disease-resilient phenotype in DMD [ 51 ]. In addition, it has been demonstrated that AMPK stimulation led to some beneficial effects in the skeletal muscle of DMD experimental models, including the reduction of skeletal muscle fragility and induction of slow-twitch myogenesis, which make the muscle phenotype more oxidative [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%